NEXT GENERATION OF PROFESSIONALS IN ECUADOR: A MANAGER'S GUIDE TO MILLENNIAL/GENERATION Z UNIVERSITY STUDENTS - Tusev, Aleksandar (2019)
Barry Salzberg, CEO of Deloitte Global, correctly predicted that “... the business community … need to change the way they engage Millennial talent or risk being left behind” (Deloitte, 2015, p. 2). By 2020, Millennials alone will make up 50% of the global workforce (PricewaterhouseCoopers [PwC], 2012). Consequently, organisations need to be prepared to adapt to the expectations of the latest generations of tech-savvy recruits, particularly when it comes to attracting, retaining and training them (PwC, 2012). Generational challenges can hardly fail to become more acute over the next decade as younger Generation Z graduates transition into the workplace. As discussed by O’Boyle, Atack and Monahan (2017), the workplace, especially entry level positions targeted at Millennial and Generation Z graduates, is changing. Entry level positions, aimed at graduates, traditionally eased employees into the workplace with light supportive duties. Today, many of the traditional trainee tasks have been replaced by technology. For example, in accounting entry level tasks used to include the filtering and classification of clients’ receipts, a timeconsuming task. However, today, technology has made it possible for receipts to be processed electronically, automatically linking them to clients’ accounts via online user-friendly platforms. As computing power continues to accelerate exponentially, (“Moore’s Law,” n.d. para. 1), coupled with the introduction of artificial intelligence, almost all aspects of the workplace are set to undergo dramatic changes. Today, graduate recruits from the Millennial and Generation Z cohorts are increasingly expected to apply their dynamic skills in the workplace from the outset, such as performing complex analytical calculations (O`Boyle et al., 2017). The generational gap between Millennials/Generation Z and older cohorts, including Generation X and Baby Boomers, is much more profound than earlier generational gaps due to the fundamental changes technology has brought with it. As discussed by Singh and Dangmei (2015), without proper understanding, organisations will have difficulty recruiting and retaining the best talent, leading to failures in motivating and inspiring them, which could negatively impact overall organisational performance. Organisations are now facing the inevitability of three of four generations working in the same space, each with their distinct attitudes, behaviours and value system. This creates a challenge for managers to encourage their current staff to transfer knowledge and build trust with the new generations of professionals entering the workplace (Bencsik, Juhász, & Horváth-Csikós, 2016). Without greater understanding of the new generations, organisations may revert to the use of stereotypes, leading to further problems. Academics and managers are increasingly focusing on studying Millennials and Generation Z cohorts. This is clear in the abundance of attention this topic has received from across academic fields and industries across the world. Since at least 2013, Deloitte, the prominent multinational accounting firm, has published annual reports on Millennials, in their Millennial survey series, aimed at helping organisations and managers better understand the latest generation of employees (Deloitte, 2013). In 2018, the Deloitte series transitioned from Millennials to Generation Z cohorts, with their report Welcome to Generation Z (Deloitte, 2018a). Deloitte referred to Millennials as those born from January 1983 until December 1994, and Gen Z as those born from January 1995 to December 1999 (p. 3). Such industry sponsored reports have helped describe and analyse Millennials and Generation Z cohorts from across the world, including Latin America. However, to date, Ecuador has received little attention. Ecuador has been developing at a rapid pace over the past few decades, seeing great strides of improvement in economic growth and stability as well as a decrease in poverty and greater investment in higher education (World Bank Group, 2017; 2018; Ramirez, 2016). Of the adult population in Ecuador, 24%1 come from the Millennial and Generation Z cohorts (Instituto Nacional de Estadística y Censos [INEC], 2010), (born from 1985 to 2000). Inevitably, these two generations will be responsible for the direction the country takes over the coming decades. Unfortunately, there is scarce information on them.